Inflorescences of Mauldinia sp. (Lauraceae) and associated fruits from the Cenomanian of Languedoc Roussillon, France. (April 2016) - Moreau, Jean-David; Gomez, Bernard; Daviero-Gomez, Véronique; Néraudeau, Didier; Tafforeau, Paul
Abstract: Inflorescences of Mauldinia (Lauraceae) are described from the middle Cenomanian Pauletian facies of Gard, Languedoc-Roussillon, south-eastern France. This is the first record of the genus from this part of Europe. Mauldinia sp. is described based on peduncles and lateral units. Isolated, slender peduncles show spirally arranged scars or rarely attached lateral units. Isolated lateral units consist of cladode-like structures showing up to seven flower/fruit scars. Some isolated fruits were found associated with peduncles and lateral units. Fruits are ovoid fruits contain a single, elongated seed. The pericarp consists of epicarp, mesocarp and endocarp. The seed consists of two cotyledons containing well-developed reserve cells. Mauldinia sp. from Gard differs from known Mauldinia species by having longer internodes along the peduncle and by the shape of the lateral units. Sedimentological and palaeontological evidence suggests that Mauldinia sp. from Gard grew in a protected, littoral environment with limited marine influence. This report provides new information to the relatively poorly known Cretaceous record of angiosperms in France. The occurrence of Mauldinia in the lower Upper Cretaceous of Gard corroborates the widespread occurrence of the genus in marginal littoral environments during the mid-Cretaceous. Highlights: Inflorescences of Mauldinia are described from the Cenomanian of France. It consists of the first record of the genus from this part of Europe. Preservation of specimens provides details of cuticle and histology. Peduncles, lateral units, and fruits differ from known Mauldinia species. Mauldinia from the Cenomanian of France grew in littoral environments.